PEDAGOGICAL HERMENEUTICS: A NEW FOUNDATION IN THE INTERPRETATION AND APPLICATION OF CHRISTIAN RELIGIOUS EDUCATION (CRE) - Udur Ernita Aritonang; Kelly Simanjuntak; A. Dan Kia (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Pedagogical Hermeneutics seeks to bridge the gap between the biblical text and the educational context through a dialogical process involving the educator, the learner, and the Word of God. In this approach, interpretation does not merely focus on the historical and theological meaning of the text but also on the existential transformation of the learner involved in it. Pedagogical Hermeneutics emphasizes that every process of faith learning is an act of interpretation oriented toward personal and communal transformation. Christian education does not stop at the transfer of biblical knowledge but becomes a reflective space in which learners encounter the living God through the text. The educator acts as a facilitator who helps learners interpret life experiences in the light of the Gospel so that the meaning of the Bible is not reduced to mere information but becomes inspiration and life transformation. This approach also demands an integration between modern hermeneutical theories such as those of Gadamer and Ricoeur and contextual Christian pedagogical praxis. Pedagogical Hermeneutics, therefore, reaffirms the function of the Bible not only as a theological text but also as an educational text that shapes faith consciousness. This paper aims to affirm the relevance of the hermeneutical approach in faith learning that is reflective, participatory, and transformative. This study employs a qualitative descriptive method through theological and pedagogical literature analysis.